Pengaruh Reward, Komunikasi dan Penguasaan Teknologi terhadap Produktivitas Kerja Karyawan pada PT. Allianz Star Network Medan - Ruth Deanta Tarigan; Purnama Yanti Purba; Rizal Suganda; Frendi Novensius Purba; Novy Rachma Herawati (IPM2KPE, 2024)
This research aims to test and analyze the influence of rewards, communication and mastery of technology on employee work productivity at PT Allianz Star Network Medan. This research uses a quantitative approach with descriptive research and explanatory research. The sampling method was carried out using saturated sampling, and data analysis used multiple linear regression. The research results show that partially, at PT Allianz Star Network Medan, rewards have a positive and significant effect on employee work productivity, communication has a positive and significant effect on employee work productivity, and mastery of technology has a positive and significant effect on employee work productivity. Simultaneously, rewards, communication and mastery of technology also have a positive and significant influence on PT Allianz Star Network Medan. In conclusion, this research provides an important contribution to the understanding of the factors that influence employee work productivity in this company. The implications of the results of this research can be used as a basis for developing more effective human resource management policies and practices at PT Allianz Star Network Medan. Keywords: Communication, Mastery of Technology, Employee Work Productivity